Gender differences in gait kinematics in runners with iliotibial band syndrome. Issue 6 (26th January 2015) - Phinyomark, A.; Osis, S.; Hettinga, B. A.; Leigh, R.; Ferber, R.
Abstract : Atypical running gait biomechanics are considered a primary factor in the etiology of iliotibial band syndrome (ITBS). However, a general consensus on the underpinning kinematic differences between runners with and without ITBS is yet to be reached. This lack of consensus may be due in part to three issues: gender differences in gait mechanics, the preselection of discrete biomechanical variables, and/or relatively small sample sizes. Therefore, this study was designed to address two purposes: (a) examining differences in gait kinematics for male and female runners experiencing ITBS at the time of testing and (b) assessing differences in gait kinematics between healthy gender‐ and age‐matched runners as compared with their ITBS counterparts using waveform analysis. Ninety‐six runners participated in this study: 48 ITBS and 48 healthy runners. The results show that female ITBS runners exhibited significantly greater hip external rotation compared with male ITBS and female healthy runners. On the contrary, male ITBS runners exhibited significantly greater ankle internal rotation compared with healthy males. These results suggest that care should be taken to account for gender when investigating the biomechanical etiology of ITBS.